A new species of the genus Afissa Dieke, 1947 (Coleoptera, Coccinellidae) from China - Lezhi Wang; Qifan Yang; Quan Zhang; Xingmin Wang (Biodiversity Data Journal)
Recent morphological and molecular studies have clarified some aspects of the taxonomy of Afissa Dieke, 1947, but many species remain unexamined or misclassified. Additional taxonomic work is essential to resolve the classification and distribution of Afissa species in Asia, particularly in China.Afissa xuexii sp. nov. is described from Yunan and Guizhou Province, China. This new species is characteried by its typical bifurcated penis guide. Diagnosis, description and illustrations are provided.